2013
DOI: 10.1182/blood.v122.21.1651.1651
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine Arabinoside Chemotherapy Does Not Enrich For Leukemic Stem Cells In Xenotransplantation Model Of Human Acute Myeloid Leukemia

Abstract: Despite a high rate of complete remission after treatment with conventional genotoxic agents, the overall survival of patients with acute myeloid leukemia (AML) is poor due to frequent relapses caused by the chemoresistance of rare leukemic stem cells (LSCs, also called Scid-Leukemia Initiating Cells). This unfavorable situation leads to a strong need to characterize those cells in order to target them with new specific therapies. Using a robust immunodeficient mouse model (NOD/LtSz-scid IL2Rγchainnull or NSG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…11 Furthermore, immune-deficient mice bearing primary human AML xenografts have recently shown that the relative reduction of functionally defined LSCs can be similar to the reduction of bulk blasts upon challenge with cytarabine. 12 This finding suggests that LSCs are not always refractory to chemotherapy that targets dividing cells, which in practice has been known for many years, based on the observation that core binding factor AML is particularly sensitive to high doses of cytarabine 13 and can be cured with this approach. 14 Taken together, the collective data indicate that in some cases LSCs share the normal hematopoietic stem cell (HSC) property of cell-cycle quiescence, but that in a variety of circumstances they may also display a more active cell-cycle profile.…”
Section: Lscs Are Quiescentmentioning
confidence: 99%
“…11 Furthermore, immune-deficient mice bearing primary human AML xenografts have recently shown that the relative reduction of functionally defined LSCs can be similar to the reduction of bulk blasts upon challenge with cytarabine. 12 This finding suggests that LSCs are not always refractory to chemotherapy that targets dividing cells, which in practice has been known for many years, based on the observation that core binding factor AML is particularly sensitive to high doses of cytarabine 13 and can be cured with this approach. 14 Taken together, the collective data indicate that in some cases LSCs share the normal hematopoietic stem cell (HSC) property of cell-cycle quiescence, but that in a variety of circumstances they may also display a more active cell-cycle profile.…”
Section: Lscs Are Quiescentmentioning
confidence: 99%
“…The CSC hypothesis would predict that this is caused by the presence of chemotherapy resilient AML subpopulations. Previous studies with informative paired diagnostic and relapse samples have already suggested that relapse arises from re‐emergence or clonal evolution of a pre‐existing clone generated before treatment and whose clonal selection is shaped by chemotherapy (Ding et al , ; Parkin et al , ; Perry et al , ). These studies and others hint to the fact that both the dominating clone at diagnosis as well as pre‐existing AML subclones have to be eradicated to control the disease.…”
Section: Relapse‐relevant Leukemic Stem Cells (Lscs) Are Already Pres...mentioning
confidence: 99%